O trabalho do assistente social no "terceiro setor": a superação das dificuldades e a construção de caminhos - Silva, Lídia Lopes da (2008)
When society changes, a new way of life begins, and with it new human needs arise; in order to deal with them, professionals reorganise themselves and seek new strategies for a more effective role. This research starts from the fact that it is time to rethink about the social worker space and seeks to contribute to the professional exercise, particularly in the third sector , a field which has grown notably in the last decade, despite being little studied. To better know the social workers' work possibilities in the third sector, we have adopted a quantitative research with four carers representing such sector. As results we have reached the profile limits of those entities, defined by Law as Social Care entities, and have found the trace of religiosity and a remarkable dedication in attending to children and teenagers. During this research, financial resources were given priority, in which we have found that tha State is the major investor to the development of these activities; we have also examined other factors such as management, resource funds and volunteers participation. Analysing the social workers professional performance in the third sector and its peculiarities, we have thought about topics such as activities, planning, autonomy and work value, enhancing the social care network and the citizen's view about private and public spaces. We have studied the professionals' capacity and their political interest as an answer to the labour market difficulties, however we have noticed that this participation is only seen in the legal counselling sector. These professionals highlight a good relation with the council social care network and their local knowledge, which helps to further the institutional space, resulting from the necessity for better care and appliance of rights